Comparison of Choroidal Thickness in Primary Open Angle Glaucoma Patients in the Late Phase After Trabeculectomy and Without Trabeculectomy: Enhanced Depth Imaging Optical Coherence Tomography Study - (:unkn) unknown (My University, 2016)
Primer açık açılı glokomu olup trabekülektomi sonrası geç dönemde olan olgular ve cerrahi geçirmemiş hastalarda koroid kalınlıklarının karşılaştırılması: Artırılmış derinlik görüntüleme optik koherens tomografi çalışmasıAmaç: Bu çalışmanın amacı açık açılı glokomlu hastalardan trabekülektomi cerrahisi uygulanmış olanları (TRAB) ve cerrahi geçirmeyenleri (POAG) koroid kalınlıkları açısından artırılmış derinlik görüntüleme optik koherens tomografi (EDI-OKT) kullanarak karşılaştırmaktır.Gereç ve Yöntem: Kesitsel, non-randomize klinik olgu serisi olarak planlanan çalışmaya en az 6 ay önce trabekülektomi cerrahisi geçirmiş 12 hastanın 14 gözü ve primer açık açılı glokomlu 12 bireyin 20 gözü dahil edildi. Uveit, diyabetik retinopati, yaşa bağlı makula dejenerasyonu, optik nöropati veya başka bir retina, koroid veya optik sinir hastalığı bulunanlar ile belirlenmiş sınırların dışında bir refraksiyon kusuru olan bireyler çalışmaya dahil edilmedi. Tam bir göz muayenesini takiben koroid kalınlığı RTVue-100 5.1 (EDI-OKT) cihazı ile; retina pigment epitelinin hiperreflektif dış bandı ile skleranın iç yüzeyi arasından, sırasıyla subfoveal alandan ve subfoveal alanın 1.5 mm temporal ile 1.5 mm nazalinden ölçüldü.Bulgular: Çalışmaya dahil edilen hastaların yaş ortalaması TRAB grubunda 59.9±13.4 , POAG grubunda 58.4±9.7 idi. Yaş, cinsiyet, lateralite, GİB, kırma kusuru, görme keskinliği, aksiyel uzunluk ve SKK açısından gruplar arasında istatistiksel olarak anlamlı fark saptanmadı (p>0.05). Ortalama Koroid kalınlığı TRAB grubunda subfoveal, temporal ve nazalde (sırasıyla 388.2±84.1, 372.4±77.1, 374.1±84.1 µm) POAG grubuna göre (sırasıyla 383±64, 358.6±62, 357.5±61.5 µm) daha yüksek ölçüldü fakat istatistiksel olarak anlamlı değildi (p>0.05). POAG grubunda GİB ile subfoveal ve nazal koroid kalınlıkları arasında orta seviyede negatif korelasyon saptandı. (sırasıyla: p=0.048, r=-0.458; p=0.042, r=-0.458)Sonuç: Subfoveal ve perifoveal koroid kalınlığı trabekülektomi sonrası geç dönemdeki bireyler ile hiç operasyon geçirmemiş, medikal tedavi ile GİB regüle, primer açık açılı glokom tanılı kişiler karşılaştırıldığında istatistiksel olarak anlamlı farklılık göstermemektedir. POAG hastalarında, GİB yükselmesine koroid incelmesi eşlik edebilir.

Comparison of choroidal thickness in primary open angle glaucoma patients in the late phase after trabeculectomy and without trabeculectomy: enhanced depth imaging optical coherence tomography studyObjective: The aim of this study is to compare choroidal thickness using enhanced depth imaging optical coherence tomography between primary open angle glaucoma patients with or without previous trabeculectomy.Material and Method: Fourteen eyes of 12 patients with a history of previous trabeculectomy surgery (TRAB) at least 6 months ago and 20 eyes of 12 patients who has a diagnosis of primary open angle glaucoma (POAG) and did not experience trabeculectomy surgery were recruited to this cross-sectional non-randomised study. Patients with a history of uveitis, diabetic retinopathy, age related macular degeneration, refractive errors other than the determined limits, optic neuropathy or other retinal, choroidal or optic nerve diseases were excluded. Following the complete ophthalmologic examination, choroidal thickness was measured between the hyperreflective outer layer of retinal pigment epithelium and inner layer of sclera, at subfoveal region and 1.5 mm temporal and 1.5 nasal to the fovea, respectively, using RTVue-100 5.1 (EDI-OCT) device.Results: The mean age of the patients in the TRAB group was 59.9±13.4 , while it was 58.4±9.7 in POAG group. Groups showed homogeneous distribution in terms of age, gender, laterality, IOP, refractive errors, visual acuity, axial length and central corneal thickness (CCT) (p>0.05). The mean subfoveal, temporal and nasal choroidal thickness of TRAB group was higher (388.2±84.1, 372.4±77.1, 374.1±84.1 µm, respectively) compared to the POAG group (383±64, 358.6±62, 357.5±61.5 µm, respectively), but the difference was not statistically significant (p>0.05). There was a moderate negative correlation between IOP and subfoveal and nasal choroidal thickness in patients with POAG (p=0.048, r=-0.458; p=0.042, r=-0.458; respectively)Conclusion: There was not any statistically significant difference regarding subfoveal and perifoveal choroidal thickness between patients with previous trabeculectomy at least 6 months ago and patients with diagnosis of POAG who had medically regulated IOP rates and did not experienced trabeculectomy. Patients with POAG may experience choroidal thinning in case of high IOP rates.
Primer açık açılı glokomu olup trabekülektomi sonrası geç dönemde olan olgular ve cerrahi geçirmemiş hastalarda koroid kalınlıklarının karşılaştırılması: Artırılmış derinlik görüntüleme optik koherens tomografi çalışması
Keywords: Cerrahi